2001
DOI: 10.1063/1.1370368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal and hydrogen treatment on indium segregation in InGaN/GaN multiple quantum wells

Abstract: The effects of indium segregation and hydrogen on the optical and structural properties of InGaN/GaN multiple quantum wells, grown by metalorganic chemical vapor deposition were investigated. Photoluminescence and high-resolution transmission electron microscopy analysis showed that two types of indium-rich regions can be formed in the InGaN well layers. Self-assembled quantum dot-like indium-rich regions were found in the well layer grown at a normal growth temperature. These regions behaved as luminescent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…that strive for smooth planar morphology and sharp interfaces within the InGaN/GaN stack. The growth of GaN barriers at elevated temperature [5], and introducing hydrogen ðH 2 ) during barrier growth [6,7] are believed to be the most efficient approaches for improving the surface morphology and thermal stability of InGaN/GaN QWs.…”
Section: Introductionmentioning
confidence: 99%
“…that strive for smooth planar morphology and sharp interfaces within the InGaN/GaN stack. The growth of GaN barriers at elevated temperature [5], and introducing hydrogen ðH 2 ) during barrier growth [6,7] are believed to be the most efficient approaches for improving the surface morphology and thermal stability of InGaN/GaN QWs.…”
Section: Introductionmentioning
confidence: 99%
“…In the work (Yong-Tae Moon et al, 2001) it was shown also that the GIs+H2 decrease In content in the upper part of InGaN layer that results in short wavelength shift of the emission. However, in the case of growth thin InGaN QWs effect of the GIs is more complex and leads to modification of microstructure of whole InGaN QW (Tsatsulnikov et al, 2011a).…”
Section: Effect Of Hydrogen On Ingan Qw Formationmentioning
confidence: 99%
“…This is a dominant effect for moderate quality structures and it was a driving force for our first experiments on GI+H2. In the works (Liu et al, 2003;Moon et al, 2001) it was shown that the admixing of hydrogen during GIs leads to elimination of the excess of In atoms with InGaN surface and improve structural quality of an InGaN.…”
Section: Effect Of Hydrogen On Ingan Qw Formationmentioning
confidence: 99%
“…2,30 The common explanation is that charge carriers are somehow localized and thus nonradiative recombination at dislocations is significantly reduced. The presented mechanisms for localization may concern (1) only a few atoms, holes, or chains of such, 31 (2) nanoscale non-random clustering of In atoms, i.e., by spinodal decomposition, 32,33 or even (3) nanoscale fluctuations in the QW width, which could localize carriers. 34 The quantum dots that have been presented herein are larger (>20-30 nm) than the In-rich clusters commonly observed after spinodal decomposition (>2-5 nm), but remain an organized (non-random) clustering of In atoms.…”
Section: -5mentioning
confidence: 99%